Manta ray watching tourism in Eastern Indonesia: Is it sustainable?. (April 2019) - Hani, M S; Jompa, J; Nessa, M N; White, A T
Abstract: Manta ray watching tourism has become a popular tourist attraction over the past two decades, with a number of destinations offering different encounter experiences for tourists. This type of attraction has drawn worldwide attention because it can offer significant contributions to the local economy through snorkelling and diving services. Since its early development, a number of scientists have conducted research on the impacts of manta ray watching tourism, and have reported different findings regarding its sustainability. Based on published scientific articles, this study provides a literature review of manta ray watching tourism and examines the sustainability of its operation. This paper also highlights manta ray tourism hotspots in Indonesia including Nusa Penida, Komodo, and Raja Ampat as the study locations. Interviews with ten key persons including government officials, tourism operators, community, and non-governmental organization were conducted to collect and identify their perceptions. This study demonstrates different impacts of economy, ecology, and social-cultural aspects. Furthermore, different study areas apply different management approach in managing their tourist in terms of manta ray watching tourism operation. In conclusion, good governance, regulations/law enforcement, and collaborative management are significant factors to achieve sustainable manta ray watching tourism.